Clinical decisions in neuro-ophthalmology - Burde, Ronald M; Savino, Peter J; Trobe, Jonathan D (Mosby Year Book, 1992)
The publication focuses on clinical decision making in neuroophthalmology. Intended for professional public.
Keywords: oftalmologie; neurooftalmologie; nemoci nervového systému; klinické rozhodování; Nervous System Diseases; Clinical Decision-Making; neurologie; oční nemoci; Eye Diseases